The National Library And The Peruvian University - Arbulú, Ricardo (Universidad del Pacífico, 1977)
In the chronological history of the National Library, the most recent research -- of the professor in Spain and American History in Universidad Central de Madrid, Luis Martín – indicates as the oldest origin the Library Of The Order Of The Jesuits inside the school Máximo de San Pablo, in 1568, in the urban area formed by the streets or, more exactly, blocks denominated “Cascarilla” (today, the fourth block of Abancay Avenue), the drugstore San Pedro (today the fourth block of Antonio Miró Quesada Street), The Cat (today the fourth block of Azángaro Street) and The Studies (today, fourth block of Ucayali Street).